Structure of the native supercoiled flagellar hook as a universal joint - Takayuki Kato (Nature Portfolio, 2019)
The bacterial flagellar hook is a molecular universal joint that connects the rotary motor and long helical propeller of the bacterial flagellum. Here the authors present the 3.6 Å resolution cryo-EM structure of the native supercoiled Salmonella hook that provides insights into the dynamic changes of subunit conformations and intermolecular interactions of the hook protein FlgE.